Serum Uric Acid Revealed a U-Shaped Relationship With All-Cause Mortality and Cardiovascular Mortality in High Atherosclerosis Risk Patients: The ASSURE Study - Cang, Yan; Xu, Shaojie; Zhang, Jingyin; Ju, Jingyi; Chen, Zijun; Wang, Keke; Li, Jue; Xu, Yawei (Frontiers in Cardiovascular Medicine, 2021)
Background: Previous studies have demonstrated association between hyperuricemia and cardiovascular disease (CVD). Framingham study has confirmed patients with high atherosclerotic risks (HAR) had worse prognosis. However, after adjusting confounding factors, the association between serum uric acid (SUA) and all-cause mortality, cardiovascular mortality remains controversial, especially in HAR patients. Objective: The aim of this study was to reveal the SUA relationship with all-cause and cardiovascular mortality in HAR patients. Methods: The multi-center cohort study comprised 3,047 participants the follow-up was 68.85±11.37 months. Factors related to cardiovascular and all-cause mortality were tested by multivariate Cox regression analysis. Restricted cubic splines (RCS) with knots were used to explore the shape of dose-response relationship with SUA and hazard risk (HR) of all-cause and CVD mortality. Adding transformed SUA by RCS to Cox regression model, and calculation predicting all-cause, CVD mortality score. Survival receiver operating characteristic curve were implemented by regression model predicting score. Results：The SUA demonstrated “U-shaped” relationship with all-cause and cardiovascular mortality. SUA predicting all-cause and CVD mortality, cut-off value was ( >370.5 μmol/L, male), ( >327.65 μmol/L, female), and ( < 180.5 μmol/L, male), ( < 165.7 μmol/L, female). The survival ROC indicated SUA predicted all-cause and CVD mortality, the AUC was 0.702 and 0.711. HR of all-cause mortality (male and female) with hyperuricemia and hypouricemia was 2.08 and 2.01; 2.04 and 1.98, respectively; HR of CVD mortality (male and female) was 2.09 and 1.79; 2.02 and 1.89; respectively. Conclusion：Abnormal SUA levels were significant and independent risk factors for all-cause and CVD mortality. Hyperuricemia and hypouricemia all increased mortality whether male or female. Routine SUA evaluation and intensive management are needed in HAR patients.